PENERAPAN PASAL 55 UNDANG-UNDANG NO. 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (STUDI DI UNIT PPA SAT.RESKRIM POLRESTABES MEDAN) - Gabriellah Angelia Gultom; Madiasa Ablisar; Muhammad Ekaputra; Chairul Bariah (Universitas Sumatera Utara, 2018)
ABSTRACT Domestic Violence is not a new thing. Moreover the issue of Domestic Violence (KDRT) concerns also the issue of human rights. The existence of domestic violence can be caused by the lack of respect in fulfilling basic human rights. These basic human rights include equal rights and obligations within the law. The criminal acts of domestic violence committed by a husband to his wife or otherwise are often regarded as common in a family. Usually if there is domestic violence, both the perpetrator and the victim cover it. Because it would be considered a disgrace for their family. In fact, the act of violence is an act that violates the law and of course the perpetrators may be subject to criminal sanctions set forth in Law no. Law No. 23 of 2004 on the Elimination of Domestic Violence. All forms of domestic violence, in the event that the proof is stipulated in Article 55 of the PKDRT Law, which provides that as a valid evidence, the testimony of a victim witness is enough to prove that the defendant is guilty, if accompanied by a valid evidence others. This means that even the victim's witnesses who testified that he or she experienced domestic violence by their husbands or wives plus a valid evidence, the husband or wife as perpetrators can be held accountable in criminal cases. In addition to being added with one piece of evidence, domestic violence should be done within the scope of the household. Keywords : Criminal Act; Domestic Violence; and Polrestabes Medan. PENDAHULUAN